2013
DOI: 10.1007/s11910-012-0328-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of Peripheral Nerves

Abstract: Over the last decade, neuromuscular ultrasound has emerged as a useful tool for the diagnosis of peripheral nerve disorders. This article reviews sonographic findings of normal nerves including key quantitative ultrasound measurements that are helpful in the evaluation of focal and possibly generalized peripheral neuropathies. It also discusses several recent papers outlining the evidence base for the use of this technology, as well as new findings in compressive, traumatic, and generalized neuropathies. Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 80 publications
4
101
1
13
Order By: Relevance
“…Another weakness is that we could not follow our patients longitudinally and assess the implications of the findings regarding treatment. The choice of abnormality parameters may be disputed in favor of relative indices or individually corrected cut‐off values, but we decided to rely on the minimal existing consensus and accept CSA at the carpal tunnel inlet as a principal diagnostic index . We included the FRT, as some earlier studies indicated that this parameter may be abnormal independently from CSA .…”
Section: Discussionmentioning
confidence: 99%
“…Another weakness is that we could not follow our patients longitudinally and assess the implications of the findings regarding treatment. The choice of abnormality parameters may be disputed in favor of relative indices or individually corrected cut‐off values, but we decided to rely on the minimal existing consensus and accept CSA at the carpal tunnel inlet as a principal diagnostic index . We included the FRT, as some earlier studies indicated that this parameter may be abnormal independently from CSA .…”
Section: Discussionmentioning
confidence: 99%
“…In that case, preclinical detection of motor axon loss is possible by either physiologically (e.g., needle electromyography) or by imaging studies. Among noninvasive imaging studies, sonography has been reported to be useful in detecting morphological abnormalities, such as abnormal thinning/swelling as well as fascicular involvement in various neuromuscular diseases (13).…”
Section: Sonographic Evaluation Of Peripheral Nerves In Als and Relatmentioning
confidence: 99%
“…Ultrasound provides a view of the anatomy of nerve as well as of surrounding structures and allows real-time and painless assessment of median nerve entrapment. Typical findings associated with nerve compression include enlargement of the nerve proximal to the site of compression, decreased echogenicity, and increased vascularity [10]. Moreover ultrasound enables precise differentiation of the space occupying lesions causing median nerve compression [11].…”
Section: Discussionmentioning
confidence: 99%